Composição química e atividades biológicas das folhas de Eugenia involucrata DC - Toledo, Adrieli Gorlin (2018)
Scientific researches with Brazilian native species have aroused a growing interest in the search for active compounds with biological potential. The fruit species Eugenia involucrata DC. (Myrtaceae), known as “cerejeira-do-mato”, is popularly used in the form of tea with antidiarrheal and digestive action. In the literature, although researches with the fruit because to its commercial value, studies with the leaves of the species are scarce, being few data related to the biological activities of this plant. Therefore, the objective of this work was to identify the chemical components of the essential oil by gas chromatography coupled to mass spectrometry (GC-MS) and to perform the phytochemical exploration of the plant extracts through colorimetric visualization and / or precipitate formation. In addition, the antimicrobial activity by the broth microdilution technique and the antioxidant activity by the 2,2-diphenyl-1-picryl-hydrazyl (DPPH) method were evaluated. In the analysis of the essential oil by GC-MS 28 compounds were identified, all sesquiterpenes, corresponding to 89.41% of the essential oil. The antimicrobial activity of the oil was observed for all Gram-positive bacteria tested and for yeast C. albicans. The essential oil presented a reduction capacity of DPPH up to 66.81%, evidencing its antioxidant potential. The phytochemical prospection of the extracts detected the presence of saponins, steroids, flavonoids and tannins. The antimicrobial and antioxidant activities were observed in all extracts tested. The extracts that presented the best results were: methanolic with antimicrobial activity between 3.12 and 25 mg.mL-1 and antioxidant percentage of 95.85% in the concentration of 1.0 mg.mL-1; and the ethanolic with antimicrobial activity between 3.12 and 50 mg.mL-1 and antioxidant activity of 92.84% in the concentration of 1.0 mg.mL-1. It is suggested that the biological activities found for the essential oil are related to its major compounds: elixene (26.53%), β-caryophyllene (13.16%), α-copaene (8.41%) and germacrene D (7.17%). Regarding the extracts, due to the proven presence of flavonoids and tannins, it is suggested that these phenolic compounds are related to the activities found.